2018
DOI: 10.1002/dta.2495
|View full text |Cite
|
Sign up to set email alerts
|

A rapid non‐target screening method for determining prohibited substances in human urine using liquid chromatography/high‐resolution tandem mass spectrometry

Abstract: Target analysis using liquid chromatography-tandem mass spectrometry is applied for rapidly detecting various prohibited doping substances. Frequent modification is required as additional substances are prohibited. We developed and validated a non-target screening method requiring no further modification because it analyzes the full spectrum of data in fixed m/z ranges. Urine samples were extracted using solid-phase extraction and analyzed by employing a method that combines full scan and variable data indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Yet, optimization of multi‐analyte test methods is ongoing, particularly concerning throughput and robustness, supporting faster turnaround times, the implementation of new/additional analytes and metabolites, and reduced manual workload. A comprehensive and rapid ITP was presented by Han et al, who reported on the detection of a total of 111 substances and corresponding metabolites, belonging (amongst others) to the classes of diuretics and masking agents, stimulants, beta‐blockers, and narcotics on the WADA's Prohibited List . Urine samples were enzymatically hydrolyzed prior to mixed‐mode weak cation exchange SPE, and extracts were concentrated and injected into a LC‐HRMS(/MS) employing a Q/Orbitrap mass analyzer.…”
Section: Diuretics and Other Masking Agents Stimulants Narcotics Amentioning
confidence: 99%
“…Yet, optimization of multi‐analyte test methods is ongoing, particularly concerning throughput and robustness, supporting faster turnaround times, the implementation of new/additional analytes and metabolites, and reduced manual workload. A comprehensive and rapid ITP was presented by Han et al, who reported on the detection of a total of 111 substances and corresponding metabolites, belonging (amongst others) to the classes of diuretics and masking agents, stimulants, beta‐blockers, and narcotics on the WADA's Prohibited List . Urine samples were enzymatically hydrolyzed prior to mixed‐mode weak cation exchange SPE, and extracts were concentrated and injected into a LC‐HRMS(/MS) employing a Q/Orbitrap mass analyzer.…”
Section: Diuretics and Other Masking Agents Stimulants Narcotics Amentioning
confidence: 99%
“…These fall into several categories, each with distinct pharmacological profiles, chemical properties, and year‐by‐year increasingly specific requirements for their detection 2 . With recent technological advances in both liquid chromatography and mass spectrometry (LC‐MS), a great deal of effort has been directed toward development of multiclass initial testing procedures (ITP) to streamline analytical workflows in antidoping laboratories 3–32 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the second group does require preconcentration via liquid–liquid extraction (LLE) or solid phase extraction (SPE), which may or may not be preceded by enzymatic deconjugation. For this reason, multiclass ITPs had initially been developed utilizing triple quadrupole mass spectrometry (LC‐MS/MS) and two complimentary preparations such as dilute‐and‐shoot 3–12 and extraction‐based total fraction assays 13–32 . A comprehensive review has been provided by Thevis et al 33 wherein the former methods would typically cover diuretics, stimulants, narcotics, β‐blockers, and some of the β 2 ‐agonists, whereas the latter would focus on anabolic agents, hormone modulators, fentanyl analogs, synthetic cannabinoids, and glucocorticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, there had been a move towards using high‐resolution mass spectrometry (HRMS) for the detection of target analytes, leveraging on mass accuracy to filter out unwanted background peaks or noise and at the same time having the option to retrospectively analyse the stored data for untargeted drugs 11,13,16,18,19,22–27 . This paper describes a sensitive ultra‐high‐performance liquid chromatography–high‐resolution mass spectrometry (UPLC–HRMS) method performed on equine urine after SLE for the detection of 124 drugs and/or their metabolites.…”
Section: Introductionmentioning
confidence: 99%